2008
DOI: 10.2215/cjn.01260308
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Outcomes of Contrast-Induced AKI Following Computed Tomography

Abstract: Background and objectives: Most studies of contrast-induced acute kidney injury (CIAKI) have focused on patients undergoing angiographic procedures. The incidence and outcomes of CIAKI in patients undergoing nonemergent, contrastenhanced computed tomography in the inpatient and outpatient setting were assessed.Design, setting, participants, & measurements: Patients with estimated glomerular filtration rates (GFRs) <60 ml/min per 1.73 m 2 undergoing nonemergent computed tomography with intravenous iodinated rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
128
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(136 citation statements)
references
References 29 publications
5
128
1
2
Order By: Relevance
“…Using a prospective design, routine repeat serum creatinine determinations 48 to 72 h after contrast, six definitions of contrast-induced AKI (CI-AKI), and the electronic medical record of the VA health care system, Weisbord et al (4) were able to determine the incidence of CIN and its long-term consequences in a group of patients who received intravenous contrast media for CT imaging. The minority of patients received any prophylaxis, in the form of intravenous saline before and/or after contrast exposure, use of N-acetylcysteine, or advice regarding discontinuation of nephrotoxins.…”
mentioning
confidence: 99%
“…Using a prospective design, routine repeat serum creatinine determinations 48 to 72 h after contrast, six definitions of contrast-induced AKI (CI-AKI), and the electronic medical record of the VA health care system, Weisbord et al (4) were able to determine the incidence of CIN and its long-term consequences in a group of patients who received intravenous contrast media for CT imaging. The minority of patients received any prophylaxis, in the form of intravenous saline before and/or after contrast exposure, use of N-acetylcysteine, or advice regarding discontinuation of nephrotoxins.…”
mentioning
confidence: 99%
“…reported that administration of contrast agent beyond the maximum acceptable dose (contrast agent 5 mL/kg × body weight [kg]/serum creatinine) can increase the risk of nephropathy. A high incidence of contrast nephropathy has been reported at doses >100 mL 5. The onset of acute renal failure in ischemic bowel disease has been reported to increase the mortality rate 6.…”
Section: Discussionmentioning
confidence: 99%
“…Computed tomographic angiography has a high accuracy for the diagnosis of SMA occlusion (up to 95–100%). However, there might be issues with the use of contrast agents 5, 6. Magnetic resonance angiography requires a long time for imaging 1.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have identified a baseline eGFR <45 mL/ min per 1.73 m 2 to be associated with an increased risk of contrast-induced nephropathy. 10,11 We therefore excluded patients with an eGFR below baseline. No significant AR was observed with postoperative ultrasound cardiography (UCG) in the AVNeo group.…”
Section: Study Population and Designmentioning
confidence: 99%